2004
DOI: 10.1002/uog.952
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the fetal nasal bone at 11–14 weeks of gestation by three‐dimensional ultrasound

Abstract: Objective To evaluate the benefit of three-dimensional (3D)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 7 publications
2
30
0
Order By: Relevance
“…Indeed, multiple attempts were required to obtain a satisfactory 3D volume in many cases because about onethird of the initial volumes obtained were considered suboptimal and excluded from further offline analysis. These observations are in keeping with those of Rembouskos et al, 14 who were the first to study 3D data sets for evaluation of the nasal bones in the first trimester. However, in their study, identification of the nasal bones in the coronal plane was achieved in only 5% of the 20 3D data sets, highlighting the importance of optimizing sonographic quality during the time of the 3D volume acquisition and not merely relying on the quality of the 2D images.…”
supporting
confidence: 89%
“…Indeed, multiple attempts were required to obtain a satisfactory 3D volume in many cases because about onethird of the initial volumes obtained were considered suboptimal and excluded from further offline analysis. These observations are in keeping with those of Rembouskos et al, 14 who were the first to study 3D data sets for evaluation of the nasal bones in the first trimester. However, in their study, identification of the nasal bones in the coronal plane was achieved in only 5% of the 20 3D data sets, highlighting the importance of optimizing sonographic quality during the time of the 3D volume acquisition and not merely relying on the quality of the 2D images.…”
supporting
confidence: 89%
“…Good interobserver agreement on nasal bone assessment was achieved when a 3D volume was analyzed by different examiners [109]. Another study [108], however, found that demonstration of the nasal bones at 11-14 weeks of gestation in a reconstructed section is entirely dependent on obtaining a good initial 2D view prior to 3D acquisition.…”
Section: The Nasal Bonementioning
confidence: 97%
“…Other authors found a signifi cant relation between incidence of NB absence and NT thickness MoM, CRL, and ethnic group [4,7,8,13,[22][23][24][25] . Perhaps the measure of NB was more powerful than only the evaluation of the presence or absence of NB.…”
Section: Discussionmentioning
confidence: 99%